Using Administrative Data to Evaluate Municipal Reforms : An Evaluation of the Impact of Minas Facil Expresso - Bruhn, Miriam (World Bank, Washington, DC, 2015)
Efforts to make it easier for firms to register formally are the most common form of business regulatory reform over the past decade. While there is evidence that large reforms have resulted in some increases in registration rates, recent experimental evidence suggests very few informal firms choose to register when given information about how to do so. This raises the question of whether it is productive for governments to continue to extend simplification efforts to all firms, especially those in more remote areas where many of the benefits of registering may be reduced. This study uses administrative data to evaluate the impact of Minas Facil Expresso, a program in the state of Minas Gerais, Brazil, which attempted to expand a business start-up simplification program to more remote municipalities. Using difference-in-differences with 56 months of registration data for 822 municipalities, the analysis finds introducing these units actually led to a reduction in registration rates, and no change in tax revenues. The paper uses this evaluation to illustrate the design choices and issues involved in using administrative data to evaluate reforms, with the goal of also providing a template that can be used for evaluating similar reforms elsewhere.